Bioarchaeological remains as indicators of costly signalling: two case studies from the Middle Bronze Age of Central Italy. Issue 4 (8th August 2017) - Silvestri, L.; Achino, K. F.; Gatta, M.; Rolfo, M. F.
ABSTRACT: This paper concerns the role of costly signalling in the ritual expressions of Middle Bronze Age human culture of Central Italy. A wide overview of the existing literature and the accurate examination of recent case studies enabled us to demonstrate that costly signalling is especially identifiable through the study of the ecofactual remains found in caves that are central ritual sites in Apennine protohistory. The dozens of perinatal domesticates from Grotta Mora Cavorso and the quintals of burnt seeds from Grotta di Pastena, had they not been considered in their burial and strongly ritual framework – which has been identified with certainty also thanks to these ecofacts – could have provided only a general and highly unreliable palaeoenvironmental and palaeoeconomic subsistence reconstruction. The same remains, analysed in a social perspective, have allowed us to recognize a complex set of symbolic practices and to clarify some possible features of the society that performed these rituals.